Clinicopathologic Characteristics of Head and Neck Squamous Cell Carcinoma in Puerto Ricans - Busquets, José M.; García, Héctor A.; Trinidad-Pinedo, Juan; Báez, Adriana (Puerto Rico Health Sciences Journal, 2011)
see manuscript